2021
DOI: 10.3389/fendo.2020.534343
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphic Distribution of Hypothalamic Tachykinin1 Cells and Their Innervations to GnRH Neurons in the Zebrafish

Abstract: Substance P (SP) and neurokinin A (NKA), encoded by TAC1/Tac1 gene are members of the tachykinin family, which exert their neuromodulatory roles in vertebrate reproduction. In mammals, SP and NKA have been shown to regulate gonadotropin-releasing hormone (GnRH) and luteinizing hormone (LH) secretion via kisspeptin neurons. On the other hand, the role of SP/NKA in the regulation of reproduction in non-mammalian vertebrates is not well known. In the present study, we first localized expression of tac1 mRNA in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 105 publications
(126 reference statements)
1
5
0
Order By: Relevance
“…Early studies have found that SP injection could enhance the learning ability of goldfish through dopamine mediation [30]. Another research showed that the SP/NK1R system is involved in osteogenesis and sexually differential localized expression of tac1 in the brain in zebrafish [31,32]. Recent studies have found that SP and NKA can promote the Lh and Prl secretion through NK1R and NK2R at the grass carp pituitary cells, which proves that tac1 encoding products are involved in the regulation of reproductive function in fish [33].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have found that SP injection could enhance the learning ability of goldfish through dopamine mediation [30]. Another research showed that the SP/NK1R system is involved in osteogenesis and sexually differential localized expression of tac1 in the brain in zebrafish [31,32]. Recent studies have found that SP and NKA can promote the Lh and Prl secretion through NK1R and NK2R at the grass carp pituitary cells, which proves that tac1 encoding products are involved in the regulation of reproductive function in fish [33].…”
Section: Discussionmentioning
confidence: 99%
“…SP and NKA can regulate the secretion of GnRH and LH. They play a neuromodulatory role in reproductive processes in vertebrate animals ( Arisawa et al, 1989 ; Ogawa et al, 2021 ). SP signaling in TAC1 neurons is linked to kisspeptin signaling at the level of GnRH neurons to regulate fertility in male mice ( Maguire et al, 2017 ), but the regulation of GnRH by SP may be the opposite in different species; for example, in crested newt, SP has been shown to downregulate GnRH and attenuate the pituitary secretion of LH ( Gobbetti et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…22 Because VP release from SCN neurons is activity dependent, 19,20 these observations suggested there might be differences in the firing pattern of SCN VP neurons in the two sexes. Indeed, sexually dimorphic features of the SCN have been reported in several species, [28][29][30][31][32][33][34] including humans, 35 and sex differences in circadian physiology are well documented. [35][36][37][38][39][40] Therefore, the goal of this study was to characterize and compare the circadian profiles of electrical activity in identified SCN VP neurons of male and female rats.…”
Section: Discussionmentioning
confidence: 99%